Condensed-phase Effects on the Structural Properties of Friedel-Craft RF'-BF3 - Helminiak, Heather M.; Knauf, Robin R. (My University, 2010)
The project examined the structural properties of RF'-BF3 complexes, with an eye toward solvent effects and their role in Friedel-Crafts reactions.
Color poster with text, diagrams, and graphs.
Keywords: Reactivity (Chemistry); Solvents; Solvation; Friedel-Crafts reaction; Posters